Is “English” A Knowledge? In-Depth Outlook of Proto-Indo-European, Plurilingual, and Pluricultural - Sultan Bagus Firmansyah (Alphabet: A Biannual Academic Journal on Language, Literary, and Cultural Studies, 2022)
Through the lens of “Pluri”, “Inter”, and “Bi”, this research scrutinizes English multiplicity via ethnological features. The current article tries to uncover whether English is a knowledge by offering proofs from proto-Indo-European inference, proto-northwest Germanic changes, proto West Germanic changes, as well as old English to Modern English maturation. The discussion will then moves to using Chomskyan parameters to show how English could be a knowledge. The discussion will comprise aspects of English related to phonology, morphology, syntax, semanctics, and pragmatics. Pieces of evidence presented in the discussion of the topic will answer what ‘kind’ of science English is.